2015
DOI: 10.1002/cbic.201500113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Ketoreductase Exchanges as a Means of Rationally Altering Polyketide Stereochemistry

Abstract: Modular polyketide synthases (PKSs) are multidomain multienzymes responsible for the biosynthesis in bacteria of a wide range of polyketide secondary metabolites of clinical value. The stereochemistry of these molecules is an attractive target for genetic engineering in attempts to produce analogues exhibiting novel therapeutic properties. The exchange of ketoreductase (KR) domains in model PKSs has been shown in several cases to predictably alter the configuration of the β-hydroxy functionalities but not of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 53 publications
1
44
0
Order By: Relevance
“…A recent RLS study focused on exchanging non-epimerizing A1-KRs with a panel of epimerizing A2 and B2 KRs confirmed the limitations of this method to introduce functional epimerase activity. Out of the sixteen epimerizing KRs swapped into the DEBS KR6 position, only two retained any activity [ 81 ]. A current hypothesis based on proteolytic analysis of modules with epimerizing and non-epimerizing KRs suggests that epimerizing modules may possess a more open architecture, which is important for proper KR functioning.…”
Section: Ketoreductase: Modular Context and Catalysismentioning
confidence: 99%
“…A recent RLS study focused on exchanging non-epimerizing A1-KRs with a panel of epimerizing A2 and B2 KRs confirmed the limitations of this method to introduce functional epimerase activity. Out of the sixteen epimerizing KRs swapped into the DEBS KR6 position, only two retained any activity [ 81 ]. A current hypothesis based on proteolytic analysis of modules with epimerizing and non-epimerizing KRs suggests that epimerizing modules may possess a more open architecture, which is important for proper KR functioning.…”
Section: Ketoreductase: Modular Context and Catalysismentioning
confidence: 99%
“…This motif is absent from A-type ketoreductases that form 3L-3-hydroxyacyl-ACP intermediates. Ketoreductase domains also determine methyl stereochemistry after incorporation of branched extenders (Weissman et al, 1997;Valenzano et al, 2009;Zheng et al, 2013;Annaval et al, 2015). Additional amino acid residues have been identified that allow prediction of C-2 methyl as well as C-3 alcohol stereochemistry in an extended chain (Keatinge-Clay, 2007).…”
Section: Polyene Biosynthesis and Polyketide Stereochemistrymentioning
confidence: 99%
“…Most of the focus has been directed at the reductive domains through either domain swapping or mutagenesis. Whole PKS reductive loops have been successfully swapped to alter the stereochemical outcome of a truncated product from a bimodular PKS [67,3]. Using similar bimodular PKSs for screening, site-directed mutagenesis of the amphotericin ketoreductase afforded a change in stereochemistry [155].…”
Section: Promiscuity and Engineering Of Pks/nrps Assembly Linesmentioning
confidence: 99%